The Application of the Diﬀerential Inequalities Method for Proving the Existence of Moving Front Solution of the Parabolic Equations System - N. T. Levashova; A. A. Melnikova; S. V. Bytsyura (Моделирование и анализ информационных систем)
Investigations of initial boundary value problems for parabolic equations solutions are an important component of mathematical modeling. In this regard of special interest for mathematical modeling are the boundary value problem solutions that undergo sharp changes in any area of space. Such areas are called internal transitional layers. In case when the position of a transitional layer changes over time, the solution of a parabolic equation behaves as a moving front. For the purpose of proving the existence of such initial boundary value problem solutions, the method of diﬀerential inequalities is very eﬀective. According to this method the so-called upper and lower solutions are to be constructed for the initial boundary value problem. The essence of an asymptotic method of diﬀerential inequalities is in receiving the upper and lower solutions as modiﬁcations of asymptotic submissions of the solutions of boundary value problems. The existence of the upper and lower solutions is a suﬃcient condition of existence of a solution of a boundary value problem. While proving the diﬀerential inequalities the so-called ”quasimonotony” condition is essential. In the present work it is considered how to construct the upper and lower solutions for the system of the parabolic equations under various conditions of quasimonotony.